Exploring green pedagogy for eco-centric praxis-based learning in higher education (Journal of Applied Learning and Teaching, 2025)
In the wake of climate change affecting all aspects of global sustainable development, the imperative for greening education as a tool to help address its impacts has become increasingly pressing. Facing this challenge requires global adoption of more sustainable practices, coordination of efforts, and recognizing the pivotal role that education must play. Green pedagogy can help foster a sense of agency among individuals to acquire the skills and the right attitude to catalyse the transition towards a greener future. For an eco-centric praxis-based education system to be applicable, the interconnectedness of climate change should be recognized, and a holistic perspective should be adopted. This paper proposes a systems-based approach to eco-pedagogy and the greening of curricula. Systems thinking recognizes the interconnected and interdependent relationships that exist within an emergent ecosystem. This approach can also aid an understanding of eco-pedagogy that supports and integrates an interdisciplinary conceptualization of pedagogical approaches. To effectively engage with green pedagogy, both the inherent possibilities and challenges of an eco-centric praxis-based education must be explored.In doing so, we argue that to improve the quality and the delivery of education responses to climate crisis, the integration of project-based, learner centred, experiential learning, reflective/critical learning, problem-based, and collaborative learning pedagogies can empower learners to become agents of change and contribute effectively to a more sustainable future. The proposed study aims to provide guidance on how to develop relevant, research-based curricula,  increase educators’ preparation and enhance institutional capacity to provide greening education and engage with a more eco-centric praxis-based education system. By elucidating best practices, this paper seeks to contribute to the advancement of applicability of green pedagogy in higher education and its role in building Education for Sustainable Development (ESD) competence among learners developing an eco-centric consciousness.